Cicadas (Insecta: Hemiptera: Cicadidae) of Mindanao, Philippines, with the description of a new genus and a new species - Lee, Young June (Zootaxa, 2010)
This paper provides the first faunal checklist for the family Cicadidae (Insecta: Hemiptera) from Mindanao, Philippines, comprising 17 species belonging to 13 genera. A new species, Chremistica kyoungheeae sp. nov., is described. Platypleura elizabethae Lee and Nelcyndana tener (Stål) are newly added to the cicada fauna of Mindanao. Dokuma Distant syn. nov. is treated as a junior synonym of Oncotympana Stål, which is redefined to include four species: O. pallidiventris Stål, O. viridicincta Stål, O. nigristigma (Walker) comb. nov., and an undescribed Oncotympana sp., all from the Philippines. Dokuma consobrina Distant syn. nov. is synonymized with O. viridicincta. A new genus, Sonata gen. nov., is described to include the following species previously placed in Oncotympana: Sonata fuscata (Distant), Sonata maculaticollis (De Motschulsky), Sonata ella (Lei & Chou), Sonata expansa (Walker), Sonata mahoni (Distant), Sonata melanoptera (Distant), Sonata obnubila (Distant), Sonata stratoria (Distant), and Sonata virescens (Distant) (nine species comb. nov.). The genus Champaka Distant stat. rev. is resurrected from junior synonymy with Platylomia Stål to include the following species previously placed in the Platylomia spinosa group: Champaka spinosa (Fabricius), Champaka abdulla (Distant), Champaka viridimaculata (Distant), Champaka nigra (Distant), Champaka virescens (Distant), Champaka meyeri (Distant), Champaka wallacei (Beuk), Champaka celebensis Distant, Champaka aerata (Distant), Champaka constanti (Lee), and Champaka maxima (Lee) (eleven species comb. nov.). The genus Nelcyndana Distant, 1906 is transferred to Cicadettini from Taphurini. A key to the species of Oncotympana and information on geographic distributions of the 17 Mindanao species are provided.